V. Vakulenko-K’s Diary “I am Transforming...”: Embodiment of the Artist's Ideological and Semantic Intentions. - Maryniak, Ruslana (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Purpose. To examine the notes of the writer Volodymyr Vakulenko-K., tortured by the Russians in 2022, his selected poetry contained in the book “I am transforming... Diary of the Occupation. Selected Poetry,” through the prism of the ideological guidelines, moral and aesthetic paradigms of the artist. Methods. The methodology of the study is based on Tymofii Havryliv's proposition of the phenomenological and applied value of memoir. In distinguishing four genre types of diaries, we rely on the studies of H. Kostiuk, O. Halych, and Y. Kulinska. The comparative analysis of Vakulenko's diary notes and his poetry allowed us to outline the writer's ideological and semantic intentions as a certain integrity.Results. The article analyses the worldview, moral and aesthetic paradigms embodied in Volodymyr Vakulenko-K’s book which determine the essence of the writer's work as well as public activity. The artist, who was killed by Russians in the spring of 2022, saw Ukraine as a strong state and called on his Ukrainians to beware of the evil he openly termed ‘rashism’ in his poetry of 2008. His active involvement in the Revolution of Dignity, participation in the volunteer movement, and fervent belief in the victory of the Armed Forces in the war, even in the difficult days of late February and March 2022, are evidence of his integrity and balanced civic position. Volodymyr Vakulenko built his faith in the future of the sovereign state of Ukraine not on the emotional wave of love for his native land, but on the ability to see the continuity of statehood ideas, on the basis of which the independence of the motherland was built.  We are talking about a strong-willed personality, independent and steadfast in convictions. This is exactly the kind of Ukrainian who built, fought for, and is now defending the sovereignty of our country. Although the text of the diary reveals a vulnerable personality, an artist capable of subtly feeling the beauty of this world, Volodymyr Vakulenko's life demonstrates the strength, determination, and unwavering faith in the people of which he was a part.Conclusions. The book “I am transforming... Diary of the Occupation. Selected Poetry” by V. Vakulenko-K. is not just a record of the writer's stay in his occupied native Kapitolivka in February-March 2022, it is the artist's long struggle against Russian expansion into the Ukrainian free world, recorded in his notes and reflected in his poetry, it is determing the “rashism” as an eternal threat to Ukraine's sovereignty.